2004
DOI: 10.1002/ab.20078
|View full text |Cite
|
Sign up to set email alerts
|

Social‐cognitive mediators of the relation of environmental and emotion regulation factors to children's aggression

Abstract: Tested a theoretical model in which social cognitions about aggression partially mediated the relation of environmental and emotion regulation factors to children's aggressive behavior. An ethnically diverse sample of 778 children (57% girls) in grades 4-6 from both urban and suburban schools participated. Measures included exposure to aggression (seeing/hearing about aggression, victimization), emotion regulation (impulsivity, anger control), social cognitions about aggression (self-evaluation, selfefficacy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 61 publications
8
68
2
3
Order By: Relevance
“…In terms of witnessing violence, Orue et al (2014) found that exposure to violence in 8-12 year old children increased later aggressive behaviour, and that this process was mediated by PSYCHOPATHY AND MORAL DISENGAGEMENT 7 normative beliefs about aggression. Similar findings were reported Guerra, Huesmann, and Spindler (2003) and Musher-Eizenman, Boxer, and Danner et al (2004).…”
Section: Psychopathy and Moral Disengagementsupporting
confidence: 91%
“…In terms of witnessing violence, Orue et al (2014) found that exposure to violence in 8-12 year old children increased later aggressive behaviour, and that this process was mediated by PSYCHOPATHY AND MORAL DISENGAGEMENT 7 normative beliefs about aggression. Similar findings were reported Guerra, Huesmann, and Spindler (2003) and Musher-Eizenman, Boxer, and Danner et al (2004).…”
Section: Psychopathy and Moral Disengagementsupporting
confidence: 91%
“…Furthermore, they found that such relationships were mediated through the effect of exposure to violence on emotional regulation (for victims) and social cognitions supporting aggression (for aggressors). Similarly, although not specifically about bullying, Guerra et al [2003] and Musher-Eizenman et al [2004] found a significant relationship between exposure to community violence and aggressive behavior mediated by normative beliefs supporting aggression. It is likely that those who are exposed to violence in their community learn that aggression, including bullying, is a legitimate way to reach personal goals [see also Espelage et al, 2000].…”
Section: Introductionmentioning
confidence: 84%
“…In the third study with a sample of 778 fourth through sixth graders, Musher-Eizenman et al [30] found that the relation between anger control and physical aggression was mediated by latent structures of SIP (aggressive fantasizing, retaliation approval). Latent knowledge structures are distinct from on-line SIP in that latent mental structures (i.e., beliefs, attitudes, scripts, schemas) contain information about past experiences and affect each step of on-line, or ''real-time'', decision processes [8].…”
Section: Social Information Processing As a Mediator Between Emotion mentioning
confidence: 99%